(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate treatment outcomes in patients with non-Hodgkin lymphoma treated with the R-CHOP regimen at Can Tho Oncology Hospital. Subjects and Methods: A descriptive study, combining prospective and retrospective approaches, was conducted among 50 patients with non-Hodgkin lymphoma treated with the R-CHOP regimen at Can Tho Oncology Hospital between March 2021 and June 2025. Evaluation parameters included treatment response following chemotherapy, overall survival, chemotherapy-induced toxicity, and prognostic factors for survival. Results: After the final chemotherapy cycle, the complete response (CR) rate was 58%, the partial response (PR) rate was 42%, and no cases of disease progression were recorded. The median overall survival was 33 months. Common toxicities observed during treatment included anemia, leukopenia, and elevated liver enzymes. Prognostic factor analysis indicated that disease stage, LDH levels, and the International Prognostic Index (IPI) were associated with patient survival. Conclusion: The R-CHOP regimen yields high response rates and relatively favorable survival times in patients with non-Hodgkin lymphoma, with toxicities generally remaining within acceptable limits. Disease stage, LDH levels, and the IPI are significant prognostic factors for survival.